Establishing and promoting a site for image sales - Homoláčová, Jindřiška (2019)
AbstractThe bachelor thesis deals with marketing strategy for selling children's pictures and promoting the web on the Internet.The aim of the bachelor thesis is to create a guide to creating a website and propose a way of its promotion, evaluate and propose improvements and further evaluate the business (non-profit) intention. The goal of the site is not to generate profit (in the first phase) but to raise awareness about it. Achieve traffic and offer images for sale based on the results (second phase).The partial goal is to describe how the site was created, to calculate the cost of its implementation, promotion and marketing strategies, including website traffic.